Reforming EU economic governance: is `more' any better? - Renaud Thillaye; Ludek Kouba; Andreas Sachs (WWWforEurope, 2014)
Despite significant measures to reinforce the EMU's institutional set-up, there is widespread consensus that more needs to be done in order to better deal with cyclical and structural heterogeneity in the EU. Market-based adjustment mechanisms are necessary but not sufficient to advance convergence along more sustainable growth patterns. In that context, institutional reforms advancing integration in the Eurozone are often said to be desirable from an economic point of view, albeit fraught with political difficulties. This paper seeks to provide a fresh outlook on this debate by bringing forward a third, overlooked dimension, namely the feasibility, or `implementability', of governance reforms. Like national technocracies, the EU faces the risk of failure whereby the creation of institutions or the introduction of new policies do not always bring about the expected outcomes. The paper develops a multi-criteria analytical framework to assess three possible innovations of economic governance: rule-based wage coordination, contractual arrangements for reforms, and a stabilisation fund for the Euro area. The `robustness' of any proposal seeking to increase the EU's interference into national policy-making should start with a clear economic justification, while taking the dynamics of national preferences into account. However, the risks of moral hazard and institutional barriers should also be systematically internalised in the assessment. After outlining the analytical framework (section 1), the paper assesses the three tentative reforms by using a wide range of data and analyses from existing EU documentation, academic and policy literature, and opinion surveys (sections 2 to 4). Each section ends with some recommendations on the desirable scope and design of reforms. Overall, the three case studies stress the need for a careful and reasoned approach to reforming EU governance. Beyond the predictable clash of economic rationales and political hurdles, reform ideas tend to overlook the difficulties arising at the implementation stage. Diverse wage-setting systems, low administrative capacities, and statistical uncertainty for instance all warn against `more EU money' or `EU interference'. The paper, therefore, makes the case for experimental and small-scale innovations and for a much greater engagement of the public in the politics of EU coordination.
Keywords: E02; 330; EU integration; European economic policy; European governance; European Monetary Union; Good governance; Institutional reforms; Labour markets; Macroeconomic disequilibria; Multi-level governance; Welfare reform